Pendidikan Kesehatan Pencegahan Demam Berdarah Dengue Pada Mahasiswa Prodi MIK Stikes Santa Elisabeth Medan - Pomarida Simbolon; Anthonyus Anthonyus; Urim Gabriel Dinasti Laowo; Lea Sri Ita Br. P.A; Irma Novita Sari Sihotang (Pusat Riset dan Inovasi Nasional, 2023)
Dengue Hemorrhagic Fever is a disease caused by the Dengue virus which is classified as an Arthropod-borne Virus, the Flavivirus genus and the Flaviviridae family. Dengue fever is transmitted to humans through the bite of mosquito vectors from the Aedes genus, one of which is Aedes Aegypti or Aedes Albopictus. Dengue Hemorrhagic Fever can appear at any time of the year and can attack all age groups. This disease is closely related to environmental conditions and community behavior, therefore preventive measures must be taken by every community. It is very important to prevent dengue fever in all levels of society to avoid dengue fever. The targets of community service activities are students of the Health Information Management Study Program. Interview results: Some MIK Study Program students still do not understand the precautions that must be taken to avoid contracting dengue fever and therefore are at risk of contracting dengue fever. Paying attention to the results of the survey that has been carried out, efforts that can be made to increase knowledge in preventing dengue fever are through health education efforts. The aim of Health Education is to increase students' knowledge about dengue prevention. The method used to achieve the goal is to carry out health education about dengue prevention. The results of health education activities show that there is a difference in the average knowledge scores before and after implementing health education. The conclusion from community service is that there has been an increase in knowledge about dengue prevention.